Diffusion of High-Temperature and High-Pressure CH4 Gas in SiO2 Nanochannels - Cui, Shuheng; Fu, Jianfeng; Guo, Minling; Zhao, Zhixiang; Sun, Chengzhen; Wang, Yujun (Frontiers in Energy Research, 2021)
Fundamental understandings of nanoconfined methane are crucial for improving the exploitation of tight gas. In this study, diffusivity, one of the key transport properties, of high-temperature and high-pressure methane gas is examined under a confinement in the silica nanochannels by using molecular dynamics simulations with employing Einstein diffusion equation. It is found that the diffusivity of nanoconfined methane is obviously anisotropic, namely the perpendicular diffusion coefficient is lower than that in longitudinal direction. The anisotropic diffusivity of nanoconfined methane is attributed to the restricted effect of potential interactions from the atoms of walls, which is verified by analyzing the diffusivity of methane molecules in the potential wells with Lagrangian dynamics. The diffusion coefficients of nanoconfined methane decrease with the increase of atomic potentials in the wall, which can be explained from the density distributions of methane in the nanochannels. Furthermore, we reveal the dependence of the diffusivity of nanoconfined methane on the channel height and confining effect of the wall on the diffusivity of methane molecules. The obtained results can provide a molecular insight into the transport properties of methane confined in nanospace and a theoretical guidance for the efficient extraction of tight gas.